Increasing Incidence and Risk Factors for Transmission of Covid-19 in Brebes Community Health Center, Indonesia - Sutaip, Sutaip; Sutiningsih, Dwi; Adi, Mateus Sakundarno; Diyana, Sutra; Azzahra, Nur Azizah; Bailai, Puti Andalusia Sarigando; Giyantolin, Giyantolin (Poltekkes Kemenkes Tanjung Karang, Indonesia, 2023)
Introduction: Coronavirus Disease 2019 (COVID-19) is an infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). Now, COVID-19 is still a problem in Central Java. COVID-19 cases in Central Java rank third highest in Indonesia, one of which is Brebes Regency, where there have been confirmed cases leading to death, with the highest cases at the Brebes Community Health Center. Purpose: The purpose of the study was to determine the risk factors for the occurrence of COVID-19 in the work area of the Brebes CHC, Central Java. Method: This quantitative study uses an analytical observational design and a cross-sectional approach. The data is carried out using exclusion and inclusion criteria so that it is based on the desired research focus. The sample in this study amounted to 78 respondents using purposive sampling. Univariate, bivariate (Chi-square test), and multivariate data analysis were performed. Results: The results of this study were that gender, occupation, contact history, and habit of wearing masks had a significant relationship with COVID-19 cases, with a p-value of 0.046, 0.035, 0.019l, and 0.026, respectively. Meanwhile, education has no relationship with the incidence of COVID-19 (p-value = 0.379). Conclusion: Risk factors that increase the incidence of COVID-19 in the Brebes district Public Health Centre area are consistent with other studies, namely gender, occupation, contact history, and habit of wearing masks. Prevention and control of COVID-19 cases by paying attention to these risk factors and other health protocols, washing hands using soap, maintaining distance and implementing a One-Health approach through cross-sector collaboration. Latar Belakang: Penyakit Coronavirus 2019 (COVID-19) adalah penyakit menular yang disebabkan oleh Sindrom Pernafasan Akut Parah Coronavirus 2 (SARS-CoV-2). Hingga saat ini, COVID-19 masih menjadi masalah di Jawa Tengah. Kasus COVID-19 di Jawa Tengah menduduki peringkat ketiga tertinggi di Indonesia salah satunya Kabupaten Brebes yang telah terkonfirmasi kasus meninggal dunia dengan kasus tertinggi di Puskesmas Brebes. Tujuan: Mengetahui faktor risiko terjadinya COVID-19 di wilayah kerja Puskesmas Brebes Jawa Tengah. Metode: Penelitian ini merupakan penelitian kuantitatif dengan desain observasional analitik dengan pendekatan Cross-Sectional. Sampel dalam penelitian ini berjumlah 78 responden dengan menggunakan random sampling. Analisis data dilakukan secara univariat, bivariat (uji Chi-square), dan multivariat. Hasil: Hasil penelitian ini adalah jenis kelamin, pekerjaan, riwayat kontak, dan kebiasaan memakai masker memiliki hubungan yang bermakna dengan kasus COVID-19, dengan p-value 0,046; 0,035; 0,019l; dan 0,026, masing-masing. Sedangkan pendidikan tidak ada hubungan dengan kejadian COVID-19 (p-value = 0,379). Simpulan: Faktor risiko yang meningkatkan insiden COVID-19 di wilayah Pusat Kesehatan Masyarakat kabupaten Brebes konsisten dengan studi lain, yaitu jenis kelamin, pekerjaan, riwayat kontak, dan kebiasaan memakai masker. Pencegahan dan pengendalian kasus COVID-19 dengan memperhatikan factor risiko tersebut, selain protocol Kesehatan lain, cuci tangan menggunakan sabun, jaga jarak dan menerapkan pendekatan One-Health melalui kolaborasi lintas sektor.